1996
DOI: 10.1139/v96-056
|View full text |Cite
|
Sign up to set email alerts
|

The reactions of O(3P) with some carboxylic acids and esters

Abstract: The reactions of o(~P) with formic acid, acetic acid, methyl acetate, ethyl acetate, n-propyl acetate, and isopropyl acetate have been studied kinetically as a function of temperature. The rate constants were measured in a discharge-flow system under pseudo-first-order conditions with a large excess of the organic reagent. No reaction could be found between o(~P) and either formic acid or acetic acid in the temperature range 300-420 K. The acetate esters, on the other hand, reacted with 0c3P) at readily measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…(a) and (b) compare the two H-abstractions from MA by O atom. Figure (c) depicts the total rate constants for the two reactions and compares them with two sets of experimental rate coefficients by Caravan et al (green triangles) and Mix et al­(blue crosses).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(a) and (b) compare the two H-abstractions from MA by O atom. Figure (c) depicts the total rate constants for the two reactions and compares them with two sets of experimental rate coefficients by Caravan et al (green triangles) and Mix et al­(blue crosses).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Similarly, MRACPF2 predicts larger barrier heights than CCSD­(T) for MA + O, and hence the rate constants with MRACPF2 energies are lower for both reactions A and B, as depicted in Figure (a and b). Caravan et al (green triangles) and Mix et al (blue crosses) measured the total rate constants of MA + O ( 3 P ) in a discharge-flow system over the ranges 300–420 K and 300–430 K, respectively. Caravan et al concluded that the main contribution was H-abstraction by an O atom, especially from the OCH 3 group of MA.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of ethyl acetate, the presence of humidity improved the removal efficacy significantly. The positive effect of humidity was explained by the production of OH radicals which have higher rate constants for the reaction with ethyl acetate compared to O radicals [*1.5 9 10 -12 and *5 9 10 -15 cm 3 molecule -1 s -1 , respectively (Picquet et al 1998;Caravan et al 1996)]. In fact, Rudolph et al suggested that in dry air, the excited states of N 2 play a more important role than O radicals in the decomposition of ethyl acetate.…”
Section: Resultsmentioning
confidence: 99%